PENINGKATAN MOTIVASI BELAJAR MENGGUNAKAN MIND MAPPING DI KELAS V SEKOLAH DASAR - Pagea, Arum Sari; Marli, Suhardi; Uliyanti, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this study was to increase students' learning motivation in learning Social Sciences using the mind mapping model in class V SDN 16 Kuala Mandor B. This study used a descriptive method in the form of classroom action research (CAR) and was collaborative in nature. The subjects in this study were teachers as researchers and class V students, amounting to 14 students, this study was conducted in the even semester located in class V SDN 16 Kuala Mandor B. Data collection techniques used were direct observation. Data analysis technique used is to use the average calculation formula. This research was conducted in 3 cycles with the results of 1) the average ability of teachers to carry out learning is as follows, in the first cycle of 3.20, in the second cycle of 3.41, in the third cycle of 3.76. 2) the average percentage increase in intrinsic learning motivation in cycle I was 37.50, cycle II was 55.36 and cycle III was 78.57. 3) the average percentage increase in extrinsic learning motivation in the first cycle was 45.24, the second cycle was 61.91, and the third cycle was 85.71. From the data obtained it can be concluded that mind mapping models can increase students' learning motivation. Keywords: Learning Motivation, Mind Mapping Model, Social Sciences.